Osmanlı Dönemi’ni Konu Alan Dönem Filmleri Anlatısının Oluşturulması Sürecinde Minyatürlü El Yazmalarının Birincil Kaynak Olma Özellikleri: Elyazmalarındaki Minyatür Ve Edebi Metin Anlatısından Yararlanma - Yakut, İnci (The Turkish Online Journal of Design Art and Communication, 2015)
This study put forth the functions of Manuscripts with miniature including miniature and literary text as primary sources for Ottoman - period film narrative making process. The study consits of the units on the relationships between epic narrative and reality, Accessing to primary sources for Ottoman Empire Period Epic Film Narrative, the features of Manuscripts with miniature, an analysis on manuscript, Kıyafetü’l-Insaniyye fi Şema’ili’l-Osmaniyye. It is used critical literature review and social semiotics as medhods in this study. Miniatures and literary texts in Ottoman Empire period Manuscripts with miniature have epic and epic reality. This situation requires to be used text analysis methods on manuscripts. Scenarists and directors at cinema area must have the knowledge and skills to analyze miniatures and literary texts within manuscripts for Ottoman Empire period film narrative making. If Turkish tranlation of the manuscrits isn’t available, Scenarists and directors to know Ottoman Turkish that is the language of Ottoman period manuscripts is to provide them to analyze on texts.
Keywords: Osmanlı Dönemi; Dönem Filmi; Epik Anlatı; Epik Karakter; Epik Mekan; Gerçeklik; Minyatürlü El Yazmaları; Ottoman Period; Period Film; Epic Narrative; Epic Character; Epic Space; Manuscripts With Miniature; Reality